Evaluation of the written curriculum for residency training of the Department of Rehabilitation Medicine College of Medicine Philippine General Hospital University of the Philippines Manila - Mojica, Jose Alvin P. (1997)
Curriculum evaluation is an essential part of curriculum improvement and development. In this descriptive study, evaluation of the written curriculum was focused on two parameters, namely: determination of congruency of relationships within the curriculum and determination that the curriculum adequately prepared the resident for board certification and future practice of the specialty. The study sample consisted of 33 participants from 3 groups of stakeholders: 1) the graduates of the residency training program; 2) the department faculty members; and 3) the second and third year residents of the department. The questionnaire and focus group discussion were used as the main tools for evaluation. In addition, the department curriculum was compared with the curriculum guidelines provided by the Philippine Board of Rehabilitation Medicine (PBRM) based on Harden's Criteria (1986). Results showed that there was congruency in the different components of the written curriculum, i.e.,the objectives, subject content characteristics, organization of the learning experiences, and characteristics of the assessment procedures. However, there was apprehension from faculty members regarding the wide scope of the subject content which may not be attainable. Also, the faculty members noted missed opportunities for teaching-learning activities in the clinics. With regards to preparation of the resident for board certification, self-study and encouragement as well as pressure from the faculty members helped in preparing for the specialty board examinations while lack of time and motivation hindered preparation. Most (94%) of the graduates also noted that the training program adequately prepared them for future practice of the specialty. Comparison of the written curriculum of the department with the curriculum guidelines of the PBRM showed that the PBRM lacked structure and substance based on Harden's criteria. Based on the above findings it is concluded that the written curriculum has internal congruency and that the curriculum adequately prepares the resident for board certification and future practice. However, it is suggested that curriculum implementation be further evaluated.